2012
DOI: 10.4236/oji.2012.22008
|View full text |Cite
|
Sign up to set email alerts
|

CD38 expression on CD8+ cells—Its influence on development of tuberculosis in HIV positive individuals

Abstract: CD38 expression on CD8+ cells seems to correlate well with HIV viral-loads, while the expression levels are thought to be low in patients with tuberculosis. This study aimed at determining the levels of CD38 expression in HIV+ individuals who develop tuberculosis. Expression levels of CD8 and CD38were analysed in peripheral blood collected from HIV (73), TB (32), HIV-TB (31) and healthy controls (20). The percentage of CD8+/CD38+ cells significantly increased during the first few years of seropositivity and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(31 reference statements)
2
3
0
Order By: Relevance
“…TB had also reported to foster immune activation by increasing the expression of CD38 on T-cell subsets [30,31]. Besides, we also found that CD38 expression on both T-cell subsets inversely correlated with CD8 + T-cell counts and HIV PVL, consistent with previous findings [30,31]. Correlation analysis showed that HLA-DR expression was directly associated with T-cell counts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…TB had also reported to foster immune activation by increasing the expression of CD38 on T-cell subsets [30,31]. Besides, we also found that CD38 expression on both T-cell subsets inversely correlated with CD8 + T-cell counts and HIV PVL, consistent with previous findings [30,31]. Correlation analysis showed that HLA-DR expression was directly associated with T-cell counts.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we showed that increased expression of CD38 on T cells of HIV/TB co-infected compared to HIV-infected individuals, which is in line with others [27,29] as previously proposed due to peripheral immune activation [29]. TB had also reported to foster immune activation by increasing the expression of CD38 on T-cell subsets [30,31]. Besides, we also found that CD38 expression on both T-cell subsets inversely correlated with CD8 + T-cell counts and HIV PVL, consistent with previous findings [30,31].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that the presence of Mtb affect the C38 expression on the CD8 + cells responsible for CTL differentiation. This negatively impacts the HIV progression which may also depend on the ethnic group (genes) [19]. There have been several hypotheses set regarding the relationship between HIV specific CTLs and viral load.…”
Section: Why Cytotoxic Cells?mentioning
confidence: 99%
“…This was also consistent with existing evidences that explain the association of HIV/TB co-infection with sustained levels of peripheral activation in immune compartment following pathogenic persistence [67][68][69] . Indeed, TB infection fosters immune activation as evident from up-regulated CD38 expression on T-cell subsets as compared to uninfected subjects [66,70] . Besides this, CD38 expressions in both the CD4 + and CD8 + T-cell subsets have been inversely correlated with CD8 + T-cell counts and HIV plasma viral load, and that enhanced CD38 expression could lead to rapid HIV disease progression [66,70] .…”
Section: Co-infectionmentioning
confidence: 99%
“…Indeed, TB infection fosters immune activation as evident from up-regulated CD38 expression on T-cell subsets as compared to uninfected subjects [66,70] . Besides this, CD38 expressions in both the CD4 + and CD8 + T-cell subsets have been inversely correlated with CD8 + T-cell counts and HIV plasma viral load, and that enhanced CD38 expression could lead to rapid HIV disease progression [66,70] . The mechanism whereby MTB appears to attenuate the expression of HLA-DR, particularly on innate cells such as macrophages and DCs, is via the synthesis of bacterial proteins (such as 19kD lipoprotein and lipoprotein rG), which subsequently cause impaired antigen presentation and processing, potentially affecting the downstream signaling for HLA-DR expression on T cells [71][72][73][74] .…”
Section: Co-infectionmentioning
confidence: 99%